Effect of Coconut Fiber Dosage on Flexural Performances of Magnesium Phosphate Cement - Jiang, Zuqian; Zhang, Liwen; Zhang, Junping; Sun, Zhuo; Li, Jing (Frontiers in Materials, 2021)
Magnesium Phosphate Cement (MPC), as a new type of inorganic cementitious material, has advantages such as fast curing speed and high early strength. However, MPC displays a poor toughness as other cementitious materials. Coconut Fiber (CF) is a renewable plant fiber, appearing a potential to improve the toughness of MPC in our previous research. As a result, more studies will be followed up for investigating the mechanical behaviors of MPC mixing with CF. This paper focused on the effect of CF volume dosage on MPC’s flexural performances. Flexural strength, load-deflection (L-D) relationship, fractural patterns and flexural toughness were obtained by a three-point bending test. The results showed that flexural strength increased with CF dosage increasing firstly and then decreased, and the CF dosage of 3% was the best for flexural strength. However, toughness was increasing as CF dosage increasing continuously from the L-D relationship. Additionally, the techniques of scanning electron microscope (SEM) was employed to analysis the microstructure of MPC with different CF dosages.